Elemen dan Ekspresi Musikal dalam Memperkuat Makna Lantunan Helaehili pada Ritual Pernikahan Masyarakat Adat Sentani - Markus Rumbino (Journal on Education, 2023)
Music is said to affect one's musical emotions when listening to music through electronic devices or watching live music performances. This study aims to find out how the musical elements and expressions in helaehili chant affect the audience's musical emotions in the traditional wedding rituals of the Sentani people. The research method used to conduct this research is ethnography. This research lasted for one month in Puay village, East Sentani District and Abar village in Central Sentani District, located in Jayapura Regency, Papua Province. The informants in this study were 5 people who had broad insights regarding the customs of the Sentani people. Apart from that, the main, second and third sources were also chanters, each of whom had been singing various types of chants for the Sentani people for more than 20 years. Meanwhile, the fourth and fifth sources are traditional leaders who have an important role in the community in Puay and Abar villages. The researcher collected data by conducting a literature review, uninvolved and involved observations, semi-structured interviews, translating the audio and video data of the researcher's chanting helaehili into writing. The researcher used an H6 zoom audio recording device and a Sony camcorder to document the entire interview process. The results of this study are the musical elements and expressions expressed by helaehili singers in wedding rituals can affect the audience's musical emotions. So that listeners can enjoy and at the same time feel the impression of sadness and happiness. Thus it can be concluded that musical elements and expressions are the language of musical communication which allows for emotional musical responses between the singer and the listener.